Perkembangan Dan Pembatasan Penggunaan Bank Garansi Sebagai Jaminan Pelaksanaan Oleh Pemerintah Dan Perusahaan BUMN Dalam Pelaksanaan Perjanjian - Anwar, Azhar Rahadiyan (UI Scholars Hub, 2022)
The purpose of Banking in Indonesia is to support the development and stability of Indonesia’s economy. To achieve that and according to the rules in Indonesia, Banks have 2 (two) primary function which is to collect fund from the citizen and to distribute fund to the citizen. this kind of function is known as intermediary function of Bank. One of the product of Bank regarding the distribution fund to ctizen manifest in Bank Guarantee. Bank Guarantee is a product of Bank which has the purpose to give guarantee to the benifciary that the principal who request Bank Guarantee to the Bank would perform according to contractual obligation between beneficiary and principal. in 2013, Indonesia’s Governemnt launch a program called as “State Owned Enterprise (SOE) Synergy” with the purpose to maximize the efficiency and empowerment of SOE which led to the Cooperation between Government Agency and SOE is a priority to carry out business activities including Banking Activities or any activity related to Banking. One of the Banking activities related to business is the use of Bank Guarantee as the performance bond. In this research, the topic that will be discussed is the development and the limitation usage of Bank Guarantee by Government Agency & SOE in Indonesia regarding the SOE Synergy